THE TEACHERS’ BELIEFS IN TEACHER WRITTEN CORRECTIVE FEEDBACK ON THE STUDENTS' WRITING - Dyah Fitri Mulati; Joko Nurkamto; Nur Arifah Drajati (Universitas Bengkulu, 2020)
Examining EFL writing teachers’ beliefs is becoming an essential study since teaching is no longer being noticed merely in a behaviour term but rather as thoughtful behaviour as teachers are active, thinking decision-maker. This study addresses the teachers’ beliefs in the specific teaching writing strategy that is commonly used by the teachers in Indonesia to assist students’ writing, teacher written corrective feedback. It was designed as a case study surveying two teachers from a secondary school in Lampung as its respondents. This current study aims at (1) exploring teachers’ beliefs in providing teacher written corrective feedback both in the explicitness and the amount of feedback, and (2) describing the factors that shape teachers’ beliefs in providing written corrective feedback. The data were collected by using mixed-type questionnaire and interview adapted from Lee (2009) consisting of three items related to the beliefs in written corrective feedback, followed by the factors that shape the beliefs teachers may hold on. The findings show some underlie different beliefs regarding the explicitness and amount of teacher written corrective feedback between the teachers. However, they agreed that academic background in the secondary school and college was counted as the contributed factor that shapes their beliefs in providing written corrective feedback on students’ writing. Further, teacher added practical experience when they are teaching writing as her additional factor.